(untitled) (Agricultural Engineering, 2019)
The purpose of the paper was to determine the impact of UV-C irradiation of seed potatoes on the formation of tuber defects in the progeny crop. The field experiment was carried out in 2016-2018, and the object of research was potato plants of the Vineta, Lord and Owacja varieties. Different heights of the UV-C radiator above the chamber bottom (40-100 cm) and exposure times (1-30 min.) were used. Data was analyzed with the STATISTICA 13.3 program, at the assumed significance level α = 0.05, using a non-parametric test χ2 for multidimensional contingency tables. In the scope of the parameters of the chamber for UV irradiation of plant material adopted in the experiment, no statistically significant UV-C effect on potato tuber defects was demonstrated. In the potato tuber crop of the examined varieties, shape deformations in the form of kidney and spindle disease were identified. The crop of potato obtained from seed potatoes irradiated with UV-C demonstrated a lower percentage of deformed tubers, as compared to the control combination.